Standalone balloon aortic valvuloplasty: Indications and outcomes from the UK in the transcatheter valve era. Issue 2 (19th February 2013) - Khawaja, Muhammed Z.; Sohal, Manav; Valli, Haseeb; Dworakowski, Rafal; Pettit, Stephen J.; Roy, David; Newton, James; Schneider, Heiko; Manoharan, Ganesh; Doshi, Sagar; Muir, Douglas; Roberts, David; et al.
<x xml:space="preserve">Abstract</x> Objectives We sought to characterize UK‐wide balloon aortic valvuloplasty (BAV) experience in the TAVI era. Background BAV for acquired calcific aortic stenosis is in a phase of renaissance, largely due to the development of transcatheter aortic valve implantation (TAVI). Methods Data from 423 patients at 14 centers across the UK were analyzed. Results Patients were aged 80.9 ± 9.5 years; 52.5% were male. Mean logistic EuroScore was 27.3% ± 16.8%. Mean peak transaortic gradient fell from 62.0 ± 26.3 to 28.3 ± 16.2 mm Hg. Aortic valve area increased from 0.58 ± 0.19 to 0.80 ± 0.25 cm2 echocardiographically. Procedural complication rate was 6.3%, comprising death (2.4%), blood transfusion ≥2 U (1.2%), cardiac tamponade (1.0%), stroke (1.0%), vascular surgical repair (1.0%), coronary embolism (0.5%), and permanent pacemaker (0.2%). Mortality was 13.8% at 30 days and 36.3% at 12 months. Subsequently, 18.3% of patients underwent TAVI and 7.0% sAVR, with improved survival compared to those who had no further intervention (logrank < 0.0001). Multivariate Cox proportional hazard analysis demonstrated that survival was adversely effected by the presence of coronary artery disease (HR 1.53, 95%CI 1.08–2.17, P = 0.018), poor LV function (HR 1.54, 95%CI 1.09–2.16, P = 0.014), and either urgent (HR 1.70, 95%CI 1.18–2.45; P = 0.004) or emergent presentation (HR 3.72, 95%CI 2.27–6.08; P < 0.0001). Conclusion Balloon aortic valvuloplasty offers good immediate hemodynamic efficacy at an acceptable risk of major complications. Medium‐term prognosis is poor in the absence of definitive therapy. © 2013 Wiley Periodicals, Inc.